2013
DOI: 10.11604/pamj.2013.14.107.2302
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and Human Immunodeficiency Virus coinfection among attendants of Voluntary Counseling and Testing Centre and HIV follow up clinics in Mekelle Hospital

Abstract: IntroductionHepatitis C virus remains a large health care burden to the world. HIV and HCV coinfection is major global health concern worldwide. However, there is limited information on the prevalence of HCV/HIV co-infection in Ethiopia. The aim of the study was to assess the magnitude of HIV/HCV coinfection and the potential risk factors in attendants of voluntary counseling and testing centre and HIV follow up clinics of Mekelle hospital.MethodsA cross sectional seroprevalence survey of HCV infection was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
8
10
2
Order By: Relevance
“…In contrast, unusually high HCV prevalence was reported in blood donors from Gondar (5.8%) in 2008 [9] and from Bahir Dar (13.3%) in 2007 [8]. A similar variation was also reported, among other groups, such as VCT clients [10–12], diabetic patients [58], antenatal care (ANC) [39] and medical waste handlers [32] (Table 4). Likewise, the magnitude of anti-HCV antibody from chronic liver disease patients showed a variable prevalence rate over time with high (37.8%) in 1995 [49] and low (2.7%) in 2014 [51] (Table 4).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…In contrast, unusually high HCV prevalence was reported in blood donors from Gondar (5.8%) in 2008 [9] and from Bahir Dar (13.3%) in 2007 [8]. A similar variation was also reported, among other groups, such as VCT clients [10–12], diabetic patients [58], antenatal care (ANC) [39] and medical waste handlers [32] (Table 4). Likewise, the magnitude of anti-HCV antibody from chronic liver disease patients showed a variable prevalence rate over time with high (37.8%) in 1995 [49] and low (2.7%) in 2014 [51] (Table 4).…”
Section: Resultsmentioning
confidence: 72%
“…Ababa73450 (6.8)[66]2008Hawassa40042(10.5)[11]2011A. Ababa50018 (3.6)[53]2011Mekele17416(9.2)[12]2012D/ Tabour3955(1.3)[67]2013A.Ababa38725(6.5)[68]2013Gondar40022(5.5)[64]2013Bahirdar26959(21.9) a [100]2014Bahirdar25314(5.5)[69]Others b 2006Gondar4806 (1.3)[39]2006A. Ababa122021 (1.7)[66]2008Hawassa40024(6.0)[11]2010Jimma30430 (9.9)[58]2010Jimma30010 (3.3)[58]2010Gamo HP5561 (0.2)[33]2011Gondar2002 (1.0)[32]2011Mekele1262 (1.6)[12]2012D/ Markos4236 (1.4)[10]

a Reported as 18.9% in the original work, but the 3.0% anti-HCV antibody reported as co-infected with HBsAg was summed up and became 21.9%

b Includes antenatal care attendants, HIV voluntary counselling and testing (VCT) clients (HIV negative), VCT clients, diabetic patients, non-diabetic patients (controls for diabetic patients), out and inpatient department clients, healthcare workers and medical waste handlers, and VCT clients

Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison was not possible in Ethiopian context owing to lack of HCV seroprevalence data in HIV infected children. Although, the study population is different, previous studies in Ethiopia reported 4.5 to 9.2% HCV seroprevalence in HIV positive adults [ 28 , 29 ]. In contrast, in other studies 13.5% and 10.3% seroprevalence of HCV were reported in HIV-infected children [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 96%